Meta-analysis of the effectiveness of laparoscopic adjustable gastric banding versus laparoscopic sleeve gastrectomy for obesity - Li, Laiyuan (Medicine (Baltimore), 2019)
BACKGROUND: Laparoscopic adjustable gastric banding (LAGB) and laparoscopic sleeve gastrectomy (LSG) are common weight loss procedures. Our meta-analysis compared these procedures for the treatment of morbid obesity and related diseases. METHODS: We systematically searched the PubMed, Embase, and the Cochrane Library through January 2018. The percentage of excess weight loss (%EWL), improvement or remission of type 2 diabetes mellitus (T2DM) and hypertension were analyzed and compared. RESULTS: Thirty-three studies with 4109 patients were included. Greater decreases in excess weight were found in patients who received LSG at 6 months (weighted mean difference (WMD) −9.29, 95% confidence interval (CI): −15.19 to −3.40, P = .002), 12 months (WMD −16.67 95% CI: −24.30 to −9.05, P < .0001), 24 months (WMD −19.63, 95% CI: −29.00 to −10.26, P < .0001), and 36 months (WMD −19.28, 95% CI: −27.09 to −11.47, P < .0001) than in patients who received LAGB. However, there were no significant differences in the 3-month outcomes between the 2 groups (WMD −1.61, 95% CI: −9.96 to 6.73, P = .70). T2DM patients after LSG experience more significant improvement or remission of diabetes (odds ratio (OR): 0.22, 95% CI: 0.06–0.87, P = .03). The 2 groups did not significantly differ regarding improvement or remission of hypertension (OR 0.80, 95% CI: 0.46–1.38, P = .42). CONCLUSION: LSG is a more effective procedure than LAGB for morbidly obese patients, contributing to a higher %EWL and greater improvement in T2DM.